HUBUNGAN POWER OTOT TUNGKAI DENGAN HASIL LOMPAT TINGGI GAYA STRADDLE PADA SISWA PUTRA SDN 014 BERINGIN MAKMUR KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Hartati, Sri; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s, the ability of the student’s high jump was not optimal. Researcher found the quality of learning outcomes of sport education still low. The success of students achieving good results of high jump is explosive power leg muscles. The purpose of this research is to the correlation of explosive power leg muscles with high jump result straddle style of male students in SDN 014 Beringin Makmur Kerumutan District Of Pelalawan. Population in this research were all male students in SDN 014 Beringin Makmur amount 11 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 11 people. Research instrument is measurement of explosive power leg muscles used vertical jump test and high jump stradlle style test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : Shows that there is corelations explosive power leg muscles with the result of high jump with stradlle style.Key word : explosive power leg muscles, high jump.